1995
DOI: 10.1002/dc.2840130310
|View full text |Cite
|
Sign up to set email alerts
|

Role of fine‐needle biopsy in the diagnosis of hydatid cyst

Abstract: The cytopathologic findings in 17 patients with hydatid cyst are reported. All patients but one were referred for evaluation of a tumor mass. In 13 patients the aspirated material was diagnostic of hydatid cyst. In four patients only acellular laminated membranes were present in the aspirate and a presumptive cytopathologic diagnosis of hydatid cyst was made. Subsequent histologic studies confirmed the diagnosis of hydatidosis in all patients. No complications were encountered. Fine-needle biopsy appears a saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…FNA findings of hydatid cyst have been well defined. 7,10 Saenz-Santamaria et al 10 reported that FNAB appears to be a safe diagnostic approach in the evaluation of suspected hydatid disease. Karahatay et al 9 described a hydatid cyst of the parotid gland, which on repeated FNAB, revealed a nonspecific cyst and reported no complications.…”
Section: Discussionmentioning
confidence: 99%
“…FNA findings of hydatid cyst have been well defined. 7,10 Saenz-Santamaria et al 10 reported that FNAB appears to be a safe diagnostic approach in the evaluation of suspected hydatid disease. Karahatay et al 9 described a hydatid cyst of the parotid gland, which on repeated FNAB, revealed a nonspecific cyst and reported no complications.…”
Section: Discussionmentioning
confidence: 99%
“…The cytopathologic diagnosis of Echinococcus is established by demon-strating protoscolices, hooklets or both [3][4][5] and/or fragments of the acellular, laminated membranes. [6][7][8][9] This study investigated the role of FNAC in cases of hydatid disease with unusual locations in soft tissues, where the clinical presentation may mimic other pathologic processes such as tumors.…”
Section: Objective: To Evaluate the Role Of Fine Needle Aspiration Cymentioning
confidence: 99%
“…The patient did not show any untoward allergic reaction following FNA biopsy. Fine needle aspiration biopsy in the evaluation of suspected hydatid disease appears to be a safe diagnostic approach (15). Antiparasitic medication is widely used in the treatment protocols of surgery and may be helpful to reduce the cyst size and for elimination of the parasite.…”
Section: Case Reportmentioning
confidence: 99%